2020
DOI: 10.1177/1087054720972803
|View full text |Cite
|
Sign up to set email alerts
|

ADHD, Religiosity, and Psychiatric Comorbidity in Adolescence and Adulthood

Abstract: Objective: Religiosity has been repeatedly proposed as protective in the development of depression, sociopathy and addictions. ADHD frequently co-occurs with these same conditions. Although ADHD symptoms may affect religious practice, religiosity in ADHD remains unexplored. Method: Analyses examined data from >8000 subjects aged 12 to 34 in four waves of the Add Health Study. Relationships of religious variables with childhood ADHD symptoms were statistically evaluated. Observed correlations of ADHD symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…In one study, religiosity increased the risk of antisocial behavior such that, for religious people, ADHD was a weaker predictor of antisocial behavior. In another study, high ADHD symptoms combined with high religious participation predicted increased levels of antisocial behavior [ 11 ]. A prospective study, which examined the effect of childhood ADHD on adolescent antisocial behavior, found that a good parent–child relationship moderated and decreased the risk of antisocial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, religiosity increased the risk of antisocial behavior such that, for religious people, ADHD was a weaker predictor of antisocial behavior. In another study, high ADHD symptoms combined with high religious participation predicted increased levels of antisocial behavior [ 11 ]. A prospective study, which examined the effect of childhood ADHD on adolescent antisocial behavior, found that a good parent–child relationship moderated and decreased the risk of antisocial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…What is not clear, are the reasons other racial and ethnic minority populations are less likely to use meditation. In addition, while prayer could fall under the category of meditation, the construct for studies reviewed often use the word prayer and not meditation (Clayton-Jones & Haglund, 2016;Dew, Kollins, & Koenig, 2020;Kawachi, 2020;Ly et al, 2020). In addition, the results may reflect the fact that the respondents perceived CAM as being provider delivered instead of their self-management with CAM.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, religiosity increased the risk of antisocial behavior such that for religious people, ADHD was a weaker predictor of antisocial behavior (Novis-Deutsch et al, 2021). In another study, high ADHD symptoms combined with high religious participation predicted increased levels of antisocial behavior (Dew et al, 2020). A prospective study, which examined the effect of childhood ADHD on adolescent antisocial behavior, found that a good parent-child relationship moderated and decreased the risk of antisocial behavior.…”
Section: Interaction In the Prediction Of Antisocial Behaviormentioning
confidence: 99%